Simple ultrasonic-assisted clean graphene transfer - Zhuo-Cheng Zhang; Xiao-Qiu-Yan Zhang; Min Hu (Journal of Electronic Science and Technology, 2022)
Clean graphene transfer has received widespread research attention, where most methods are focused on cleaning the upper surface of graphene to improve the transfer technique. However, the residue formation on the bottom surface of graphene is also inevitable; therefore, cleaning the bottom surface is crucial. In this study, we proposed an improved graphene wet transfer method using an ultrasonic processing (UP) step for etching copper (Cu). Using this method, the bottom surface can be cleaned efficiently. The results of atomic force microscopy (AFM) and Raman spectroscopy mapping revealed that the graphene films transferred with UP had smoother and cleaner surfaces, less contamination, and higher quality than those transferred without UP.